An assessment of the records retention and disposition schedules of selected science high schools in Metro Manila - Regidor, Pauline M.; Aguirre, Vyva Victoria M.; Rey, Emma M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
Science high schools continue to provide quality education to deserving high school students who are gifted in science and technology. These students have given local and international recognition to the country. The study is an assessment of the retention and disposition of records for the science high schools namely, the Philippine Science High School Diliman Campus, Marikina Science High School and Mandaluyong Science High School.
The records officers and the staff of the three science high schools were interviewed. An inventory of the records of the science high schools were also done to determine the types of records created and assess their retention and disposition practices. The data gathered from the records inventory, interviews and observations revealed that: (1) the science high schools do not have a centralized records management program; (2) the records management practices of the science high schools do not conform to the standards; (3) the criteria presented is based from the insight of the records officers and staff during the course of the interview; (4) the retention and disposition practices of the science high schools need to be resolved and settled by the management.
It is important that the management has a hand in the disposal of records. The creation of a records retention and disposition schedule will serve as a guide for the removal of records in the science high school, at the same time, a records series schedule is also needed for the classification of records. In this manner, records for disposition and retention are identified and disposed based on the records series schedule. Mismanagement of records builds up stress and fosters inefficiency in the science high schools. It is necessary to systematize the arrangement, filing, and disposal of records in each office to achieve an efficient arrangement of records. Accomplishment targets are higher when records are easily tracked. By seeing the significance of having a system that involves even just a certain part of records management, such as retention and disposition schedule, these science high schools would slowly achieve the needed improvement in their records management.
Vita.
Thesis (Master of Library and Information Science)
Keywords: Philippine Science High School Diliman Campus; Marikina Science High School; Mandaluyong Science High School; Records -- Management -- Philippines -- Manila Metropolitan Area